Administrative and Legal Principles of Foreign Investment in Ukraine - H. O. Fedorov (Bulletin of Kharkiv National University of Internal Affairs)
The peculiarities of administrative and legal principles of foreign investment from the point of view of complex analysis have been considered, considering the current stage of historical development of the state system. Taking into account doctrinal research and own scientific achievements, it has been determined that nowadays it is extremely urgent to implement the whole set of practical measures aimed at achieving qualitative changes in the issues of attracting foreign investment and strengthening the control over the quality level of investments in the economy of Ukraine from the standpoint of administrative and legal principles.